Spectrophotometric Determination of Nickel(II) by Using Bis-[2,6-(2?-Hydroxy-4?-sulpho-1?-naphthylazo)]pyridine Disodium Salt - Barman, Banjit; Barua, Sudarsan (Asian Journal of Chemistry, 2010)
Bis-[2,6-(2′-hydroxy-4′-sulpho-1′-naphthylazo)]pyridine disodium salt (HSNP), a water soluble heterocyclic azo dye has been used for the trace determination of nickel(II). HSNP on complexation with nickel(II) to form a purple coloured, water soluble 1:1 complex with molar extinction coefficient (ε) 7.86 × 104 L mol-1 cm-1 at 565 nm in the pH range 6.1-9.75. Beer's law is obeyed upto 1.65 ppm of Ni(II). The optimum concentration range for determination of Ni(II) is 0.15-0.80 ppm with Sandell's sensitivity of 0.000744 (μg Ni(II) cm-2). The stability constant of the Ni(II)-HSNP complex as calculated by the Job's method in an ionic strength with respect to 0.01 M Na2SO4 solution is found to be 1.22 × 108.